2017
DOI: 10.18174/426747
|View full text |Cite
|
Sign up to set email alerts
|

Blockchain for agriculture and food : Findings from the pilot study

Abstract: 1 Furthermore, the project explored issues regarding the relevance, applicability and implications of BCT for the agrifood sector through literature study and stakeholder consultation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
79
0
10

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(101 citation statements)
references
References 6 publications
(7 reference statements)
1
79
0
10
Order By: Relevance
“…(OriginTrail 2018). Also, the project "blockchain for agri-food" developed a proof-of-concept blockchain-based application about table grapes from South Africa (Ge, et al 2017). A framework for greenhouse farming with enhanced security, based on blockchain technology, is proposed in (Patil, et al 2017).…”
Section: Food Integritymentioning
confidence: 99%
See 1 more Smart Citation
“…(OriginTrail 2018). Also, the project "blockchain for agri-food" developed a proof-of-concept blockchain-based application about table grapes from South Africa (Ge, et al 2017). A framework for greenhouse farming with enhanced security, based on blockchain technology, is proposed in (Patil, et al 2017).…”
Section: Food Integritymentioning
confidence: 99%
“…Table 2 lists potential benefits and existing barriers for the use of blockchain in agriculture and the food supply chain, as identified in Section 5 and Sections 6.1-6.5 respectively, as well as in (Chang, Iakovou and Shi 2019), (Pearson, et al 2019). A case study in the Netherlands revealed that SME lack the required size, scale or know-how needed, in order to invest in blockchain by themselves (Ge, et al 2017). Table 2: Potential benefits and existing barriers for the use of blockchain in agriculture.…”
Section: Challenges and Open Issuesmentioning
confidence: 99%
“…Although all of the papers are focused on the food supply chain, the food categories are slightly different. Most of the papers focused on agri-food supply chain in general [17,22,28,[55][56][57][58][59][60][61]. A few papers used more specific food supply chains, such as Halal supply chain [62], tilapia supply chain [63], and rice supply chain [64].…”
Section: Methodsmentioning
confidence: 99%
“…The technology is also considered and used in other fields, for example, it has been used in financial services such as online payment [16] and has been considered in other services such as smart contracts [17] and public services [18]. The Dutch Ministry of Agriculture is currently running a project called Blockchain for Agrifood that aims to explore the potential of blockchain technology in agriculture [19]. Blockchain is also used by the social enterprise "Provenance" (www.provenance.org) in the UK to record and validate certificates in agriculture supply chains.…”
Section: Related Workmentioning
confidence: 99%